L’evoluzione della percezione della mafia italiana e l’impatto di Saviano sulla stampa francese - Canto, Anne-Sophie (Comparative Cultural Studies: European and Latin American Perspectives, 2023)
The aim of this article is to show how the perception of the Italian mafia phenomenon, which was initially a paradox, has evolved over the last few years in France. Indeed, for a long time it seems to have been the object of a surprising paradox: while it was factually present on French territory, the press seemed to focus mainly on its role in Italy. However, in recent years, two events have gradually overturned this view: the attacks on the newspaper Charlie Hebdo in January 2015, and then the presence of Saviano who, as a literary and media figure, has liberated the word around the organisation and expansion of Italian organised crime.